Comparing Diagnostic Accuracy of Purple line with Transvers Diagonal of Michaelis Sacral to Predict labor Progress - Masoumeh Kordi; Morvarid Irani; Fatemeh Tara; Habibollah Esmaeily (Mashhad University of Medical Sciences, 2013)
Background and Aim: One of the key aspects of maternal care is observing the progress of labor. Careful assessment of labor progress could provide mothers to be referred on time and could decrease the maternal and neonatal morbidity. This study aimed to compare diagnostic accuracy of purple line with transvers diagonal of Michaelis sacral rhomboid to predict labor progress in nulliparous and multiparous women. Methods: In this double-blind diagnostic accuracy study, 350 nulliparous and multiparous womenwith a single pregnancy in vertex presentation and gestational age of 38-42 week, who admitted in Om-ol-Banin Hospital, Mashhad, Iran, from April to August 2012, were selected using convenience sampling. At first, the transvers diagonal of the Michaelis sacral rhomboid area was measured in cervical dilatation of ≤ 3 centimeters. Then, labor progress and presence or absence of purple lines between the buttocks in the lateral position was hourly controlled in the active phase of labor. Data were analyzed by SPSS Version 16 using Mann-Whitney and Chi-square test. Results: The mean age of the women was 25/22 (±5) years. Out of the 350 women enrolled, 61/2% were primigravidas and 38/8% were multigravidas. The presence of purple line was accompanied with normal labor progress with 68.57% sensitivity, 42.66% specificity, and 80.57% validity. The transverse diagonal of the Michaelis sacral cut-off point was ≥98.5 millimeter with 86.5% sensitivity, 59.45% specificity and 79.65% validity, which was also accompanied with normal progress of labor. Conclusion: Considering the diagnostic accuracy of transverse diagonal of the Michaelis sacral and purple line, thetransvers diagonal of Michaelis Sacral is more accurate predictor of labor progress.